Coding Betweenness in Swedish and Norwegian Translations from English - Rawoens, Gudrun; Egan, Thomas (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2015)
This paper examines the way in which the semantic notion of ‘betweenness’ is coded in Swedish and Norwegian translations of the same English source texts. The study takes its starting point in the contention that the original English expressions of ‘betweenness’ containing the preposition between constitute a viable tertium comparationis for translations of that form into the other two languages. A classification of all occurrences of between in the English source texts in The English-Swedish Parallel Corpus (ESPC) and The English-Norwegian Parallel Corpus (ENPC) in terms of the semantic role of the landmarks in the predications is followed by an analysis of the translations, both congruent and divergent. The primary focus, however, is not on the correspondences between the English original and its translations into Swedish and Norwegian, but on the parallels between the two sets of translations. To this end comparisons are drawn between the Swedish and Norwegian renderings of the various meanings of between in the source data. The analysis shows that Swedish and Norwegian resemble one another closely in the means employed to code the various senses of between. The last part of the study offers a complementary perspective in comparing occurrences of the most common translation equivalents of between, mellan in Swedish and mellom in Norwegian, in contexts where they do not translate between in the English source texts. This approach reveals that, despite the lack of between in the original texts, the two sets of translators both employ the cognate prepositions in over 25% of cases.